Numerical Examination on Impact of Hall Current on Peristaltic Flow of Eyring-Powell Fluid under Ohmic-Thermal Effect with Slip Conditions - Yasin, Maria; Hina, Sadia; Naz, Rahila; Abdeljawad, Thabet; Sohail, Muhammad (Current Nanoscience, 2023)
Aims: This article is intended to investigate and determine the combined impact of Slip and Hall current on Peristaltic transmission of Magneto-hydrodynamic (MHD) Eyring- Powell fluid. Background: The hall term arises, taking strong force-field under consideration. Velocity, thermal, and concentration slip conditions are applied. The energy equation is modeled by considering the Joule-thermal effect. To observe the non-Newtonian behavior of the fluid, the constitutive equations of Eyring-Powell fluid are encountered. Objective: Flow is studied in a wave frame of reference traveling with the wave's velocity. The mathematical modeling is done by utilizing adequate assumptions of long wavelength and low Reynolds number. Methods: The closed-form solution for momentum, temperature, and concentration distribution is computed analytically using the regular perturbation technique for the small fluid ter(A). Results: Graphical results are presented and discussed in detail to analyze the behavior of sundry parameters on flow quantities (i.e., velocity, temperature, and concentration profile). It is noticed that Powell-Eyring fluid parameters (A,B) have a significant role in the outcomes. Conclusion: The fluid parameter A magnifies the velocity profile, whereas the other fluid parameter B shows the opposite behavior.
Keywords: eyring-powell